2016
DOI: 10.1186/s40942-016-0031-1
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal thickness using EDI-OCT in adult-onset vitelliform macular dystrophy

Abstract: BackgroundTo compare choroidal thickness in patients with adult-onset foveomacular vitelliform dystrophy (AOFVD) with healthy subjects and to correlate choroidal thickness with age, gender and spherical equivalent.MethodsA prospective, observational study of 37 eyes (15 eyes in AOFVD group and 22 eyes in control group) was conducted. Images were acquired by enhanced depth imaging optical coherence tomography (EDI-OCT). Choroidal thickness measurements were performed in the subfoveal region and at 500, 1000 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…However, these authors further analyzed CT in eyes with different stages of disease and found mean choroidal thickening in the vitelliruptive stage with respect to controls, indicating that CT changes may be stage-sensitive [8]. In order to account for any stage-sensitive bias, we only included the vitelliform type and, in accordance with Palacios et al [9] and Grenga et al [8], we did not find any difference in CT between eyes with AOFVD and control eyes.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…However, these authors further analyzed CT in eyes with different stages of disease and found mean choroidal thickening in the vitelliruptive stage with respect to controls, indicating that CT changes may be stage-sensitive [8]. In order to account for any stage-sensitive bias, we only included the vitelliform type and, in accordance with Palacios et al [9] and Grenga et al [8], we did not find any difference in CT between eyes with AOFVD and control eyes.…”
Section: Discussionsupporting
confidence: 60%
“…Ref. [9] Cennamo et al showed a reduction in the choriocapillaris (CC) vascular density in eyes with AOFVD with differences in the vitelliform with respect to the vitelliruptive stage using optical coherence tomography angiography (OCTA) [10]. Even if the choroid is a predominantly vascular tissue, it is also composed of a connective structure, nerves, melanocytes, and extracellular fluid.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, while Palacios et al in 2016 demonstrated a comparable choroidal thickness between PD patients and healthy population [6], Coscas et al highlighted how subjects with wet AMD had thinner choroids compared to adult-onset foveomacular vitelliform dystrophy (AOFVD) not yet complicated by CNV, indicating a possible role in the differential diagnosis [7]. Grenga et al confirmed these findings and observed a progressive increase in the choroidal thickness based on the evolutive stage of the not yet neovascular disease, assuming a possible prognostic and pathogenetic role of the choroid in the AOFVD [8].…”
Section: Discussionmentioning
confidence: 90%